2001
DOI: 10.1111/j.1365-2796.2001.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal adverse drug events: the paradox of drug treatment

Abstract: Buajordet I, Ebbesen J, Erikssen J, Brùrs O, Hilberg T (The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 38 publications
1
30
0
3
Order By: Relevance
“…[1][2][3][4][5] ADRs cause premature deaths in older people, both in hospitals, 6 and in the community. 7 The economic burden of ADRs is considerable.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] ADRs cause premature deaths in older people, both in hospitals, 6 and in the community. 7 The economic burden of ADRs is considerable.…”
Section: Introductionmentioning
confidence: 99%
“…Even though a causal relationship is difficult to establish, the impact of DI can be very relevant. One study indicated that 4% of deaths identified in hospitalized individuals diagnosed with cancer were related to severe DIs (12) .…”
Section: Introductionmentioning
confidence: 99%
“…1000 innleggelser. Disse døds-fallene utgjorde 18 prosent av samtlige dødsfall i det aktuelle sykehuset (2,3).…”
Section: Innledningunclassified